Faith and Flux: Visionary Leadership, Tech Integration, and the Transformation of Character-Based School Culture - Muh Hambali; M. Imamul Muttaqin; Qisthi Efridita (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze how leadership grounded in religious values, along with the use of technology, contributes to creating a productive, innovative, and character-based school culture. The method used is a qualitative case study design, with in-depth interviews with the principal, vice principal, and teachers as the primary data source. Data analysis was conducted thematically using an inductive coding approach to identify emerging patterns. The results show that applying religious values in visionary leadership not only strengthens integrity, discipline, and empathy among students and teachers but also fosters a school culture grounded in moral values. Furthermore, integrating technology into learning supports innovation and improves the quality of education. However, challenges related to the digital divide and the need for teacher training must be addressed to maximize technology's potential. This study confirms that leadership grounded in religious values and the use of technology can create a more inclusive, adaptive, and sustainable education system. These findings indicate the need for an integrative strategy that digitally strengthens faith-based character education, enhances teachers' capacity as ethical digital role models, and encourages ongoing collaboration between schools and families to support student character development.